2016
DOI: 10.1016/j.molstruc.2016.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization, modal membrane interaction and anti-tumor cell line studies of nitrophenyl ferrocenes

Abstract: A series of nitrophenyl ferrocens (A1-A5) were synthesized and fully characterized in solid state (using CHN analysis, FTIR and single crystal XRD) as well as in solution phase (1 H & 13 C NMR and UV-visible spectroscopy). Micelle interface interactions of these compounds were explored and found to have ability across a micelle membrane interface. Interestingly, these compounds exhibited π-electronic push pull systems and oxidation of ferrocene to ferrocenium on crossing the negative interface of the micelle m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The replacement of an aryl ring with metal complexes, especially metallocenes has emerged as an important approach in drug discovery, resulting in significant enhancement of activity profiles . Among metallocenes, Ferrocene is considered as very attractive because of its non‐toxoicity, neutral nature and chemical stability .…”
Section: Resultsmentioning
confidence: 99%
“…The replacement of an aryl ring with metal complexes, especially metallocenes has emerged as an important approach in drug discovery, resulting in significant enhancement of activity profiles . Among metallocenes, Ferrocene is considered as very attractive because of its non‐toxoicity, neutral nature and chemical stability .…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with observations reported previously for the dipicolinate anion in micelles and reverse micelles . The quantification data revealed that pFA, MeFA and mFA have a much greater ability to penetrate into micelles than the corresponding nitro compounds . This pattern of penetration by the ferrocene compounds probably reflect the smaller dipole in the aniline compounds compared to the nitro derivative.…”
Section: Resultsmentioning
confidence: 99%
“…AOT was further dried under vacuum to remove the minute quantities of water in accordance with literature reports . The reactant nitrophenylferrocenes were prepared and characterized as described in the literature . Doubly distilled and deionized water (17.5 MΩ cm, Barnstead E‐pure) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study imparts insight into how metal complexes behave at interfaces and as solvation is altered at the nanoscale. These insights will be important in the understanding of how molecular species are affected and interact at interfaces or membranes within biological, geological, or industrial systems [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%